Computerized evaluation of recovery phase in women after bicycle test - Zumbakyte, R.; Kajeniene, A.; Vainoras, A. (International Journal of Computer Science in Sport, 2002)
There are a lot of situations when we need to evaluate features of organism reactions to load. We can investigate human organism during and after load by computerized bicycle ergometry analysis system "Kaunas - Load".